Morphogenesis of bacteriophage phi 29 of Bacillus subtilis: DNA-gp3 intermediate in in vivo and in vitro assembly. - Bjornsti, M A (1982)
The assembly of phage phi 29 occurs by a single pathway, and DNA-protein (DNA-gp3) has been shown to be an intermediate on the assembly pathway by a highly efficient in vitro complementation. At 30 degrees C, about one-half of the viral DNA synthesized was assembled into mature phage, and the absolute plating efficiency of phi 29 approached unity. DNA packaging at 45 degrees C was comparable to that at 30 degrees C, but the burst size was reduced by one-third. When cells infected with mutant ts3(132) at 30 degrees C to permit DNA synthesis were shifted to 45 degrees C before phage assembly, DNA synthesis ceased and no phage were produced. However, a variable amount of DNA packaging occurred. Superinfection by wild-type phage reinitiated ts3(132) DNA synthesis at 45 degrees C, and if native gp3 was covalently linked to this DNA during superinfection replication, it was effectively packaged and assembled. Treatment of the DNA-gp3 complex with trypsin prevented in vitro maturation of phi 29, although substantial DNA packaging occurred. A functional gp3 linked to the 5' termini of phi 29 DNA is a requirement for effective phage assembly in vivo and in vitro.